Comparison of Short-Term Efficacy Between Endoscopic Submucosal Tunnel Dissection and Endoscopic Submucosal Dissection in Treatment of Wide Esophageal Squamous Cell Carcinoma of Early Stage. Issue 6 (July 2020) - Li, Yuan; Wang, Keyi; Shi, Yanyan; Zhu, Jin; Cui, Rongli; Zhang, Hejun; Ding, Shigang
Abstract : Goal: The goal of this study was to compare the efficacy and safety of endoscopic submucosal tunnel dissection (ESTD) with endoscopic submucosal dissection (ESD) for the removal of early-stage esophageal squamous cancer wider than or equal to one half the circumference of the esophagus. Background: Although ESD has been successfully applied for resection of early-stage esophageal cancer, there are still technical challenges and postoperative stenosis when it is applied to treat large lesions. Patients and Methods: A total of 40 patients with early-stage esophageal cancer wider than or equal to one half its circumference were enrolled in this study and randomly assigned to an ESTD or ESD group for treatment of esophageal superficial squamous cell carcinoma. All of the patients received oral steroids after endoscopic dissection. We then compared the 2 groups in terms of average operating time, dissection speed, en bloc resection rate, R0 resection rate, and complications during a 1-year follow-up period. Results: The dissection speed in the ESTD group was significantly faster than that in the ESD group ( P =0.047). There were no significant differences in operating time, en bloc resection rates, or R0 resection rates between the ESTD and ESD group ( P =0.319, 1.000, 1.000, respectively). There were also no significant differences in perforation, bleeding, or stenosis rates between the ESTD and ESD group ( P =1.000, 0.748, 1.000, respectively). Conclusion: Both ESTD and ESD are safe and effective therapies for early-stage esophageal cancer wider than or equal to one half the esophageal circumference. The dissection speed of ESTD is faster than that of ESD.